Criptococose em pequenos ruminantes no Estado da Paraíba - Nascimento, Júlia Fernanda Ribeiro do (2023)
Cryptococcosis is a mycosis caused by yeasts of the genus Cryptococcus, affecting the respiratory tract and possibly spreading to the brain, other organs and skin. The infection is mainly acquired by inhalation of fungal propagules in contaminated environments containing dry bird feces, mainly pigeons, decaying wood and hollow trees. The disease occurs in humans and several animal species, being rare in small ruminants. Therefore, this work aimed to report cases of cryptococcosis in sheep and goats in the state of Paraíba. The dissertation was divided into three chapters. Chapter I is a literature review on aspects of cryptococcosis; chapter II reports the first case of disseminated cryptococcosis in sheep; and chapter III reports a case of cutaneous cryptococcosis in a goat. Case 1: Santa Inês sheep, male, four years old, with a history of lameness and increased scrotal volume that, on physical examination, showed apathy, serous nasal secretion and ulcers in the nasal cavities, severe lameness, slight increase in volume in the boletus region, subcutaneous nodules and marked enlargement of the scrotum with nodules in the testicles. Case 2: goat, SRD, female, weighing 26 kg, with chief complaint of foul-smelling liquid diarrhea. On physical examination, he presented apathy, porcelain-colored mucous membranes, presence of ectoparasites and skin lesions on the face. Then there was a productive cough, inspiratory noises and fistulation of the skin lesion. Cytology and culture of samples from both animals were performed. The cytology of both samples showed numerous yeast forms surrounded by a clear halo compatible with Cryptococcus spp., yeast colonies with characteristics of Cryptococcus spp. Due to the unfavorable prognosis, the producers opted for euthanasia. At necropsy, we observed: case 1 (sheep) – disseminated and accentuated granulomatous lesions affecting the skin and subcutaneous tissue, lymph nodes, nasal cavity, testicles and epididymis, in addition to accentuated granulomatous osteomyelitis in the incisor bones, palate, cribriform plate, bones of the carpal, nasal and frontal. Lesions consisting of large numbers of macrophages, lymphocytes, plasma cells, some neutrophils and rare multinucleated giant cells and numerous yeasts surrounded by a thick capsule; case 2 (goat) - volume increase with discrete serosanguinous secretion in the cutaneous tissue of the face, characterized microscopically as focally extensive necrosis, characterized by mononuclear inflammatory infiltrate, with some encapsulated yeasts. During the necropsy of both animals, samples were collected for fungal culture. In the culture of all samples, yeasts suggestive of Cryptococcus spp. were isolated, which were submitted to analysis by the mass spectrophotometry technique (MALDI-TOF) with positive identification for C. neoformans in sheep and C. gattii in goats. It is important to consider that, although there is no transmission of the infection between animals or from animals to humans, infected animals can contribute to environmental contamination by favoring the spread of the agent. In addition, with the confirmation of the occurrence of the disease in small ruminants in Paraíba, it highlights the importance of studies for the epidemiological characterization of the distribution of the fungus in the environment.